Patient-specific simulation of the intrastromal ring segment implantation in corneas with keratoconus. (November 2015) - Lago, M.A.; Rupérez, M.J.; Monserrat, C.; Martínez-Martínez, F.; Martínez-Sanchis, S.; Larra, E.; Díez-Ajenjo, M.A.; Peris-Martínez, C.
Abstract: Purpose: The purpose of this study was the simulation of the implantation of intrastromal corneal-ring segments for patients with keratoconus. The aim of the study was the prediction of the corneal curvature recovery after this intervention. Methods: Seven patients with keratoconus diagnosed and treated by implantation of intrastromal corneal-ring segments were enrolled in the study. The 3D geometry of the cornea of each patient was obtained from its specific topography and a hyperelastic model was assumed to characterize its mechanical behavior. To simulate the intervention, the intrastromal corneal-ring segments were modeled and placed at the same location at which they were placed in the surgery. The finite element method was then used to obtain a simulation of the deformation of the cornea after the ring segment insertion. Finally, the predicted curvature was compared with the real curvature after the intervention. Results: The simulation of the ring segment insertion was validated comparing the curvature change with the data after the surgery. Results showed a flattening of the cornea which was in consonance with the real improvement of the corneal curvature. The mean difference obtained was of 0.74 mm using properties of healthy corneas. Conclusions: For the first time, a patient-specific model of the cornea has been used to predict the outcomes of the surgery after the intrastromal corneal-ring segments implantation in real patients. Graphical abstract: Highlights: The insertion of intrastromal corneal-ring segments was simulated. The outcome of the ICRS insertion for keratoconus cornea was estimated. The simulation was compared with real post-surgery corneas. The simulated curvature of the cornea is similar to the post-surgery curvature.